Proceso de atención de enfermería en paciente de 45 años de edad con covid-19. - Trejo Vera, Jonathan Alfonso (2020)
Covid-19 is a new disease that is causing a stir in the global medical community. It was first identified in early December 2019, in a group of patients with bilateral atypical pneumonia in Wuhan, China. And vertiginously it has been spreading around the world. As of July 15, 2020, more than 13.3 million cases of the disease have been reported in 218 countries, causing countless infections and deaths and collapsing health systems. Our country, Ecuador, has not been the exception. At the end of 2020, the first case of Covid-19 was reported, making it the third country in Latin America to confirm cases of the new virus SARS-CoV-2. Since then, a precipitous increase in positive cases for coronavirus has been evidenced. The present clinical case focuses on a 45-year-old male patient who was admitted to the emergency area due to general malaise (myalgia), chest tightness, difficulty breathing, dry cough of several days of evolution, hyperthermia, pain throat, headache, loss of sense of smell (anosmia) and taste (dysgeusia), saturating 85%. It is evaluated by the treating physician and diagnosed with bilateral pneumonia and positivity for COVID-19 PCR in nasopharyngeal exudate. So he is referred to the Intensive Care Unit with respiratory failure. A care plan was carried out prioritizing nursing interventions to speed up the patient's speedy recovery. Favorable results were obtained during their hospital stay, where the patient is evaluated by the doctor and discharged under stable clinical conditions. The case is presented below, along with a review on the subject: Nursing Care Process in a 45-year-old patient with covid-19; covering relevant aspects of its incidence, clinical symptoms and treatment.